Decentralized Output-Feedback for Delayed Large-Scale Interconnected Nonlinear Systems via Dynamic High-Gain Scaling. Issue 14 (2015) - Krishnamurthy, Prashanth; Khorrami, Farshad
Abstract: A general class of nonlinear large-scale interconnected systems is considered wherein each subsystem is comprised of a nominal part in a general strict-feedback-like structure and a set of appended dynamics. The system structure is allowed to contain parametric and functional uncertainties, time delays, and a a general coupling interaction structure between dynamic components within each subsystem and across subsystems in the overall large-scale interconnected system. The controller design is based on the dual dynamic high-gain scaling technique and provides decentralized robust adaptive output-feedback delay-independent global stabilization and disturbance attenuation.